TNF Receptor 2 and Disease: Autoimmunity and Regenerative Medicine - Faustman, Denise L.; Davis, Miriam (Frontiers in Immunology, 2013)
The regulatory cytokine tumor necrosis factor (TNF) exerts its effects through two receptors: TNFR1 and TNFR2. Defects in TNFR2 signaling are evident in a variety of autoimmune diseases. One new treatment strategy for autoimmune disease is selective destruction of autoreactive T cells by administration of TNF, TNF inducers, or TNFR2 agonism. A related strategy is to rely on TNFR2 agonism to induce T regulatory cells (Tregs) that suppress cytotoxic T cells. Targeting TNFR2 as a treatment strategy is likely superior to TNFR1 because of its more limited cellular distribution on T cells, subsets of neurons, and a few other cell types, whereas TNFR1 is expressed throughout the body. This review focuses on TNFR2 expression, structure, and signaling; TNFR2 signaling in autoimmune disease and treatment strategies targeting TNFR2 in autoimmunity and the potential for TNFR2 to facilitate end organ regeneration.